Relikty leksykalne szesnastowiecznej czeskiej Biblii kralickiej w Nowym Testamencie Biblii warszawskiej (1975) - Lisowski, Tomasz (Slavia Occidentalis, 2012)
The 1975 edition of the Warsaw Bible, a modern translation from th original languages and published by the British and Foreign Biblical Society, is a translation that has superseded the Danzig Bible (Biblia Gdańska) of 1632, translated by Daniel Mikołajewski, as the authorized version to Polish-speaking Protestants in its moral guidance, observance of religious ceremonial, ecclesiastical creed and religious practice. Despite the claims of the editorial board of the Warsaw Bible, however, its translation has not entirely discarded the vocabulary of the Danzig Bible, the last link in the chain of Polish Renaissance translations that referred to the foundational doctrinal principle of the Protestant Reformation sola Scriptura. This article aims at indicating lexical relics in the New Testament of the Warsaw Bible that have their roots in the sixteenth century Czech translation of the Bible - Kralice Bible, and which were absorbed via the Danzig Bible that superseded and was much influenced lexically by the earlier Czech translation published about 50 years earlier. A section of the lexis of the New Testament of the Danzig Bible is put to an analysis in the article, namely: 1. lexemes peculiar to this particular translation, i.e., the ones that do not occur in, firstly, the New Testament in the Brześć Bible (Biblia brzeska) (1563) and in the Danzig New Testament (1606), i.e., the two earlier Protestant translations affiliated with the Danzig Bible, and, secondly, in the Bible of Jakub Wujek (1599), a Catholic post-Tridentine translation made from the Vulgate; 2. lexemes characteristic for the lexis of the New Testament of the Danzig Bible and for either of the above mentioned Protestant translations. Thus defined lexical layer of the New Testament in the Danzig Bible provided a basis for a confrontation of parallel Biblical passages in the New Testament in the Kralice Bible, which resulted in a list of 108 lexemes indicating or manifesting a potential lexical dependence of the Danzig Bible from those of the Kralice Bible . Only 25 lexemes of the total set of 108 lexemes from the New Testament in the Danzig Bible are repeated in the parallel places of the New Testament in the Warsaw Bible, whereas only 12 lexemes of the former group (i.e., 25) (after a confrontation with the parallel Biblical passages of the New Testament in the Millennium Bible, the modern Polish Catholic translation for which the Protestant Danzig Bible was not a pattern for translation), unequivocally indicate their traditional provenance. Bearing in mind the fact that the lexemes under scrutiny in the New Testament of the Danzig Bible usually occur with the frequency of f=1, the scope of the possible dependence of the vocabulary of the New Testament in the Warsaw Bible from that of the Kralice Bible via Danzig Bible, has to be evaluated as weak and insignificant. Notwithstanding the fact, the Warsaw Bible does include some lexical relics that clearly testify to the older relationships of Polish Biblical translations on account of the doctrinal sola Scriptura principle, originated within Protestants circles, with the sixteenth century Kralice Bible.